La comprensión lectora de textos académicos en el proceso formativo de los estudiantes de la carrera de Educación Básica en la Universidad Técnica de Cotopaxi, extensión La Maná, período 2014-2015. Propuesta de estrategia metodológica. - Salazar Arias, Juan Pio (2015)
The present research conducted a study of reading comprehension of academic texts in the training process of students, methodological proposal is limited to reading comprehension and cognitive integration threads that form an organic whole of interdependent phases, and highly complex, since most of the theoretical trends attach great importance to language comprehension level component structure during this process, but not the magnitude of this relationship is needed; Another study which takes into account the variation is imposed, it would be as evolutionary evidence to ontogenetic management information to deepen rather unexplored field of research. and it aims to strengthen reading and writing skills of students, to strengthen reading comprehension and production of written texts.